Further Request to release payment of 3rd interim payment application before 28th February 2021 under design contract of BRAC University new campus project - BUCG (Brac University, 2023)
This record consists of general correspondence regarding further Request to release payment of 3rd interim payment application before 28th February 2021 under design contract of BRAC University new campus project.